A mobility shift assay for DNA detection using nanochannel gradient electrophoresis. Issue 2 (7th September 2016) - Startsev, Michael A.; Ostrowski, Martin; Goldys, Ewa M.; Inglis, David W.
Abstract : Conventional detection of pathogenic or other biological contamination relies on amplification of DNA using sequence‐specific primers. Recent work in nanofluidics has shown very high concentration enhancement of biomolecules with some degree of simultaneous separation. This work demonstrates the combination of these two approaches by selectively concentrating a mobility‐shifted hybridization product, potentially enabling rapid detection of rare DNA fragments such as highly specific 16S ribosomal DNA. We have performed conductivity gradient electrofocusing within nanofluidic channels and have shown concentration of hybridized peptide nucleic acids and DNA oligomers. We also show selectivity to single base‐pair mismatch on 18‐mer oligos. This approach may enable sensitive optical detection of small amounts of DNA.